Studi Komparatif Penanganan Pandemi di Taiwan: SARS, H1N1, dan COVID-19 - Putri, Ardila; Dian Anggraeni, Silvia; Isnarti, Rika; Khairunnisa, Nisrina Najla (Department of International Relations, Brawijaya University, 2021)
Taiwan is considered as one of the countries that has successfully controlled the spread of COVID-19. Taiwan stated that their success in controlling the spread of COVID-19 was inseparable from their experience in dealing with SARS in 2003. This paper aims to compare Taiwan's response to SARS 2003, H1N1 in 2009, and COVID-19. By comparing Taiwan's response, this article detailing the transformation of Taiwan's policy in every pandemic and analyze the lesson learn for developing countries, including Indonesia, in dealing with a pandemic of communicable diseases in the future. In 2003 Taiwan had made some negligence as developing countries did when the outbreak of COVID-19. By looking at the transformation of Taiwan's policy, we can draw conclusions about the steps that developing countries can take in the future in controlling the spread of infectious diseases. This paper uses the tradition of empiricism with an indirect observation mechanism through the study of literature to describe the transformation of Taiwan's policies and analyze the lessons that can be taken by developing countries. The learning relates to communicable disease monitoring, border quarantine, communicable disease reporting, response planning, contact tracing, laboratory capacity building, public health education, open and transparent information. Keywords: Taiwan, SARS 2003, H1N1, COVID-19, Health Politics